Spatial variation of heavy metals and pathogenic bacteria in coastal waters of Davao City and IGACOS: Assessing sources, environmental impact, and health risks - Aya-ay Adorico M.; Badong Venchie C.; Badang Maria Cleofe N.; Fernandez Valerie L.; Duarte Rachel C.; Anonuevo Loreniel E.; Baslot Maria Theresa C. (E3S Web of Conferences)
The study investigates heavy metals and pathogenic bacteria in coastal sites in Davao City and the Island Garden City of Samal, Philippines, focusing on sources, environmental impacts, and health risks. Heavy metals (Cd, Cu, Fe, Pb, Mn, Zn) were quantified spectrophotometrically, while bacteria were isolated using violet red bile glucose agar. Results showed spatial variation: Cd and Zn were high in industrial zones, Cu and Mn near river catchments, and Fe in the Turtle Sanctuary. Cd and Mn levels exceeded thresholds, indicating severe pollution. Pathogenic bacteria such as Pasteurella pneumotropica were prevalent, highlighting significant health and water quality risks.